Factors Responsible For The Under-Representation Of Women In Senior High School Headship In The Brong Ahafo Region, Ghana. - Kusi, Hinneh (Advances in Social Sciences Research Journal, 2019)
The study explored factors responsible for the under-representation of women in Senior High School headship in selected districts and a municipality in the Brong Ahafo region of Ghana. This was a qualitative study underpinned by the interpretive paradigm. Specifically, a case study design was employed for the study. The sample for the study consisted of 7 purposively selected headmistresses (5 in urban centres and 2 in semi-urban centres) of the schools. A semi-structured interview schedule was employed for data collection and the collected data was analysed thematically. The study revealed that the factors responsible for women's under-representation in the school headship included female teachers' reluctance to accept responsibilities that will prepare them for headship, unfavourable and discriminatory leadership recruitment and hiring practices, and female teachers' failure to have career development plans that include headship. Among others, the study concluded that a combination of factors, including those relating to the organizations accounted for the low representation of women in school headship in the study area. Therefore, it was recommended that the secondary school authorities should collaborate with the various education directorates in the setting of the study to organise training programmes to equip potential female leaders with leadership skills so that they could apply for headship, when necessary.